2023
DOI: 10.1038/s41598-023-31870-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of cardiovascular disease risk based on major contributing features

Abstract: The risk of cardiovascular disease (CVD) is a serious health threat to human society worldwide. The use of machine learning methods to predict the risk of CVD is of great relevance to identify high-risk patients and take timely interventions. In this study, we propose the XGBH machine learning model, which is a CVD risk prediction model based on key contributing features. In this paper, the generalisation of the model was enhanced by adding retrospective data of 14,832 Chinese Shanxi CVD patients to the kaggle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Recently, Peng et al identified age, smoking status, and blood pressure as primary predictors of cardiovascular disease by developing a predictive model that utilized data from a sizable population-based study. This effective method recognized high-risk individuals [10]. The research underscores the importance of these factors in preventing and managing cardiovascular disease.…”
Section: Predictive Modeling In Cardiologymentioning
confidence: 93%
“…Recently, Peng et al identified age, smoking status, and blood pressure as primary predictors of cardiovascular disease by developing a predictive model that utilized data from a sizable population-based study. This effective method recognized high-risk individuals [10]. The research underscores the importance of these factors in preventing and managing cardiovascular disease.…”
Section: Predictive Modeling In Cardiologymentioning
confidence: 93%
“…SVM classi es data by separating classes with a boundary [26,27], whereas XGBoost is a powerful tool for classi cation and regression [27]. XGBoost has been utilized to predict outcomes such as heart failure and cardiovascular events based on patient data and risk factors, demonstrating its e ciency and accuracy in this domain [28,29]. A literature review and research articles indicate that LightGBM, a distributed gradient boosting framework known for its speed and e ciency, has been increasingly applied in healthcare and cardiovascular research.…”
Section: Model Developmentmentioning
confidence: 99%
“…Despite the clinical and research efforts over decades, cardiovascular diseases (CVD) remain a rapidly growing health problem in Western countries [1]. Atherosclerosis results in life-threatening occlusion of the blood vessels as a consequence of lipid-driven plaque buildup, characterized by endothelial activation, accumulation of oxidized low-density lipoproteins, and subsequent migration of monocytes and other inflammatory cells [2].…”
Section: Introductionmentioning
confidence: 99%